Evaluation of Canonical Inflammasome Activation in Human Monocytes by Imaging Flow Cytometry - Lage, Silvia Lucena; Dominical, Venina Marcela; Wong, Chun-Shu; Sereti, Irini (Frontiers in Immunology, 2019)
Canonical inflammasome activation is a tightly regulated process that has been implicated in a broad spectrum of inflammatory disorders. Inflammasome formation requires assembly of a cytosolic sensor protein with the adapter, ASC (apoptosis-associated speck-like protein containing a caspase activating and recruitment domain). Once formed, this multimeric protein structure allows for the activation of caspase-1, responsible for IL-1ß/IL-18 release. During this process, cytoplasmic dispersed ASC molecules cluster in one condensed micrometric-sized complex named ASC “speck,” which is widely accepted as a readout for inflammasome activation and traditionally assessed by fluorescence microscopy. However, equally reliable but less time-consuming quantitative methods have emerged as a significant need in order to improve clinical assessment of inflammasome-related conditions. Multispectral imaging flow cytometry (MIFC) combines the qualitative power of fluorescence microscopy with high throughput capabilities and multiplexing potential of flow cytometry into one single system. Here, we demonstrate that MIFC is able to assess inflammasome activation in a quantitative and statistically robust manner. We explored the optimal imaging-based tools that can be used to measure ASC speck formation and caspase-1 activation via imaging flow cytometry. We demonstrate that MIFC is able to assess inflammasome activation in a quantitative and statistically robust manner and propose that MIFC is a powerful approach to identify ASC/Caspase-1 Specks. Accurate assessment of Specks could be utilized as a biomarker in an array of human inflammatory diseases in which inflammasomes may play an important role and could help guide preventive or therapeutic strategies.